IMPLEMENTATION OF JIGSAW MODEL VISITING OUT OF CLASS IN IMPROVING STUDENTS’ LEARNING OUTCOMES OF WRITING DESCRIPTIVE (A STUDY AT THE VIII.1 STUDENTS OF SMP NEGERI 4 PADANGSIMPUAN - Della Febrina (JURNAL LINER (Language Intelligence and Educational Research), 2022)
This Classroom Action Research was motivated by the low learning outcomes of Writing Descriptive Objects in Class VIII.1 Students of SMP Negeri 4 Padangsidimpuan, which was improved by the Application of the Jigsaw Model Visiting Out of Class. The formulation of the problem in this research is